ANALISIS HARGA POKOK PENJUALAN DAN KEUNTUNGAN AGROINDUSTRI SIRUP JERUK KASTURI (STUDI KASUS PADA AGROINDUSTRI RATU KASTURI KOTA MEDAN) - Silalahi, Patresia Eirene S.A; Haryono, Dwi; Indriani, Yaktiworo (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
The main objective of this study is to examine the cost of goods sold and profits of Ratu Kasturi’s Kasturi Orange Syrup Agroindustry. The resource persons in this study are agro-industry owners, personnel of the agro-industry, and field workers at the Department of Industry and Trade of the City of Medan. Data collection was carried out in November - December 2022. Data were analyzed using descriptive quantitative analyses (cost of goods produced, cost of goods sold, and profit analysis). The method used in this research is a case study in Ratu Kasturi’s Kasturi Orange Syrup Agroindustry in Medan City. The findings of the present study showed that the cost of produced goods was IDR34,272.82/bottle and the cost of sold goods was IDR35,272.82/bottle. The selling price of Kasturi orange syrup is IDR65,000.00/bottle with a profit margin of 84.28 percent. The total profit from the sale of Kasturi orange syrup in November 2022 was IDR22,991,512.50, so this business is considered profitable. Key words: cost of goods sold, cost of goods manufactured, profits